Komparasi Konstitusi Negara Portugal dengan Negara Uzbekistan Berdasarkan Sifat, Prosedur Perubahan Konstitusi, Bentuk Negara serta Sistem Pemerintahan - Jalaludin, Iman; Erga Yuhandra; Haris Budiman; Sarip Hidayat (Indonesian Journal of Criminal Law, 2024)
The constitution is a set of principles that organize government power, the rights of the governed and the relationship between the government and the governed). In general, the constitution or basic law contains 3 (three) main points, namely: First, there is a guarantee for human and citizen rights; Second, the establishment of a fundamental constitutional structure; and Third, there is a division and limitation of constitutional tasks which are also fundamental in nature. The research method in this paper uses normative juridical research methods, namely library law research which is carried out by examining library materials or mere secondary data. In general, there are several differences between the Constitutions of Portugal and the State of Uzbekistan in terms of nature, procedures for amending the constitution, form of government, form of state, and system of government.